Factors predicting Post-Operative Facial Nerve Function following Retromastoid Vestibular Schwannoma Surgery - Adhikari, Prakash Chandra; Shrestha, Rajendra; Rajbhandari, Binod; Aryal, Sameer; Bhattarai, Sushil Mohan; Khadka, Namrata; Karki, Anjan Singh; Giri, Niraj; Lamichhane, Somraj; Jha, Rajiv (Journal of Institute of Medicine Nepal, 2025)
Introduction Facial Nerve (FN) preservation is a critical outcome measure in Vestibular Schwannoma (VS) surgery. This study aimed to identify factors predicting postoperative FN function following retromastoid VS surgery. Methods A retrospective analytical study was conducted in 30 patients with unilateral VS undergone retromastoid surgery (RMS) at Department of Neurosurgery, Bir Hospital, Nepal. Patient’s demographic data, clinical data, intraoperative tumor characteristics, and post-operative FN function status were obtained from hospital record. Results The study included 30 patients (mean age 40.7 years, 56.7% male) with unilateral VS undergone retromastoid resection. Most tumors were large (mean size 3.73 cm; 53.3% >4 cm, 70% Koos grade 4). Immediate poor FN function (House Brackmann (HB) III-VI) was observed in 76.7% of cases, improving significantly to 83.3% HB I-II by 6 months. Tumor consistency strongly influenced outcomes: firm/hard tumors had poorer immediate (p=0.001) and delayed (p <0.001) FN function compared to soft/cystic tumors. Intraoperative neuromonitoring (used in 20% of cases) improved immediate FN outcomes (p <0.001) but showed no long-term benefit (p =0.58). Age ≥30 years predicted worse immediate FN function (p =0.012). Preoperative FN dysfunction correlated with persistent poor outcomes (p <0.001). Tumor size, extent of resection, and hearing status did not significantly affect FN prognosis. One mortality (3.3%) occurred due to postoperative hematoma and hydrocephalus. Conclusion Tumor consistency was the strongest predictor, with firm tumors linked to worse outcomes. Intraoperative neuromonitoring aided early function but had limited impact on long-term recovery. Younger age and better preoperative FN status favored recovery.